Theory of Self- vs. Externally-Regulated LearningTM: Fundamentals, Evidence, and Applicability - de la Fuente-Arias, Jesús (Frontiers in Psychology, 2017)
The Theory of Self- vs. Externally-Regulated LearningTM has integrated the variables of SRL theory, the DEDEPRO model, and the 3P model. This new Theory has proposed: (a) in general, the importance of the cyclical model of individual self-regulation (SR) and of external regulation stemming from the context (ER), as two different and complementary variables, both in combination and in interaction; (b) specifically, in the teaching-learning context, the relevance of different types of combinations between levels of self-regulation (SR) and of external regulation (ER) in the prediction of self-regulated learning (SRL), and of cognitive-emotional achievement. This review analyzes the assumptions, conceptual elements, empirical evidence, benefits and limitations of SRL vs. ERL Theory. Finally, professional fields of application and future lines of research are suggested.